A study of relationship between self-concept, parents' educational background, and school climate with form 4 students' mathematics achievement - Kueh,, Bip Le. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to investigate the relationship between Mathematics achievement of Form 4 students with factors of self-concept, educational level of parents and school climate. This study was conducted quantitatively by using correlational research design. The study was conducted at a school in Sibu. The sample of the study consists of 161 Form 4 students. Questionnaire was being used as the research instrument in this study. The collected data from the questionnaire were then analyzed quantitatively by using Statistical Package for Social Science (SPSS). Cronbach Alpha’ value more than 0.7 indicated that this questionnaire was reliable. The descriptive statistics frequency and Pearson’s product-moment correlation were used to obtain the frequency, percentage, mean, standard deviation and the correlational coefficient of the independent and dependent variables.Result of this study indicated that self-concept of students (p < 0.01, r = 0.609) and school climate(p < 0.01, r = 0.431) were found to have positive significant relationship with Form 4 students’ Mathematics achievement while educational background of respondents’ parents were found to have no significant relationship with Form 4 students’ Mathematics achievement (p = 0.17, r = 0.111). Lastly, the findings were discussed based on the research objectives.